Development of Module Linear Program Based Problem Solving Assisted QSB Application - Nurhayati Nurhayati; Oswaldus Dadi (Universitas Negeri Makassar, 2020)
The purpose of this study is to obtain a linear program module based on problem solving with the help of QSB applications that meet the valid, effective and practical criteria. Type of research is a method of research and development (Research and Development) with the design model of ADDIE (Analyze, Designed, Development, Implementation, and Evaluation). The subjects of the study were Grade X students of SMK I Tanah Miring Merauke Regency, Papua Province. Module trials are carried out with stages of expert trials, legibility testing, and field trials. Experienced trials and legibility testing used a questionnaire, while field trials used the experimental one group pretest post-test design. The research instruments used were validation sheets, practical sheets, and learning achievement test sheets. The steps in this development are researching and gathering information, selecting and developing teaching materials, initial trials, revisions, main trials, and final product revisions. Product validation was validated by experts using a validation sheet. The practicality of the product is assessed by the product user, that is, the student who gets the treatment. The effectiveness of the product was tested using inferential statistical tests by looking at differences in the percentage of students' mastery learning from this cores pre-test and post-test. The results obtained by the results of validation in the category of very valid average score of student response questionnaire was 3.66 in the practical category and the percentage of percentage post-test of students 70.9% of students completed so it can be said to be effective.